Child Marriage and the Quest for Legal Protection: Integrating Islamic Family Law and Islamic Criminal Law - Irfan, M. Nurul; Rosyid, Maskur; Imron, Ali (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2026)
Child marriage remains a serious problem in Indonesia, significantly affecting children's physical safety, psychological well-being, and legal protection. This article analyzes the practice of child marriage through an integrative approach between Islamic family law and Islamic criminal law, arguing that a family law approach alone is inadequate to address the vulnerabilities and risks faced by children as victims. This research employs qualitative methods, drawing on normative studies of Islamic legal literature, national regulations, and empirical findings related to the practice of marriage dispensation. The findings demonstrate that child marriage actually involves elements of coercion, violence, and violations of children’s rights, thereby placing it within a legal domain that also aligns criminal law consideration. Consequently, a more comprehensive framework of protection is required, achieved through the integration of the regulatory function of Islamic family law with the preventive and protective functions of Islamic criminal law. Normatively, the principle of ḥifẓ al-nafs (protection of life) is invoked to underscore the primacy of children’s safety and best interests. [Perkawinan anak masih menjadi persoalan serius di Indonesia dan secara signifikan berdampak pada keselamatan fisik, kesejahteraan psikologis, dan perlindungan hukum anak. Artikel ini melihat praktik perkawinan anak melalui pendekatan integratif antara hukum keluarga Islam dan hukum pidana Islam, dengan argumen bahwa pendekatan hukum keluarga semata tidak memadai untuk mengatasi kerentanan dan risiko yang dihadapi anak sebagai korban. Penelitian ini bertumpu pada kajian normatif terhadap literatur hukum Islam, peraturan perundang-undangan nasional, serta temuan empiris yang berkaitan dengan praktik dispensasi perkawinan. Hasil penelitian menunjukkan bahwa perkawinan anak kerap melibatkan unsur paksaan, kekerasan, dan pelanggaran terhadap hak-hak anak, sehingga menempatkannya dalam ranah hukum yang juga relevan untuk dikaji melalui perspektif hukum pidana. Oleh karena itu, diperlukan suatu kerangka perlindungan yang lebih komprehensif melalui integrasi fungsi regulatif hukum keluarga Islam dengan fungsi preventif dan protektif hukum pidana Islam. Secara normatif, prinsip ḥifẓ al-nafs (perlindungan jiwa) digunakan untuk menegaskan pentingnya keselamatan dan kepentingan terbaik bagi anak.]